ByzRev 07.2025.019: Clair McPherson, Nilus of Ancyra, Byzantine Theologian and Ascetic: (Gorgias Studies in Early Christianity and Patristics 81). Piscataway: Gorgias Press 2024. - Kalvesmaki, Joel (The Byzantine Review, 2025)
Clair McPherson, Nilus of Ancyra, Byzantine Theologian and Ascetic (Gorgias Studies in Early Christianity and Patristics 81). Piscataway: Gorgias Press 2024. viii, 337 pp. – ISBN 978-1-4632-4609-9